HIGIENE DAN SANITASI JAJAN PASAR DI PASAR KOTAGEDE YOGYAKARTA - Okta Setyawanti; Sri Wahyu Andayani (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2015)
The purpose of this study to determine (1) How to Know the level of knowledge of hygiene and sanitation at  tradisional Snack vendor  are sold in the Kotagede Yogyakarta Market (2) the implementation of hygiene and sanitation on traditional snack in market Kotagede Yogyakarta. Data collection techniques used in this study is an open interview techniques to the market snack seller, techniques of direct observation and documentation techniques.  The results of this study indicate that almost entirely market Snack seller in Kotagede Market lack of knowledge about hygiene and sanitation. They have lack of understanding of the principles of sanitation. This could be possibly happened because most of them just graduated from elementary school. Most of the criteria in personal hygiene has been implemented according to the required standards. But, still there is a mismatch implementation aspects of personal hygiene, do not use special clothing for the seller or food handlers, hat or head covering is not used for work, the seller does not use an apron when working, no handkerchief to wipe the sweat or napkin to clean the workplace up. Such discrepancy is due to lack of knowledge and awareness of each seller.